2014
DOI: 10.6007/ijarbss/v4-i3/720
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stress and Burnout among Nurses in the Private Hospitals

Abstract: The purpose of this study was to explore the levels of role related stress and burnout among the nurses working in the private hospitals. Furthermore, the study also examined the relationship between role related stressors and burnout. The Maslach Burnout Inventory (MBA-HSS) and the Occupational Stress Inventory (revised edition) were used to measure burnout and role related stress. The mean scores are indicating a moderate level of stress and burnout among the nurses working in the private hospitals. Role rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…However, all three core elements of burnout (EE, DP, and PA) are found to be at moderate levels among nurses in Jordan. This result is in agreement with several previous studies which reported moderate levels of PA [ 28 ], DP [ 29 ], and EE [ 30 ].…”
Section: Resultssupporting
confidence: 94%
“…However, all three core elements of burnout (EE, DP, and PA) are found to be at moderate levels among nurses in Jordan. This result is in agreement with several previous studies which reported moderate levels of PA [ 28 ], DP [ 29 ], and EE [ 30 ].…”
Section: Resultssupporting
confidence: 94%
“…Thefindingis also in agreement withthestudies of Hansung and Madeleine (2008), who reported that job autonomy interacted with role stress in predicting burnout of social workers. The finding is also corroborated by the finding of Azeem et al (2014) who asserted that role ambiguity and other role related stressors are predictors of job burnout. Individuals who have unclear information on role are more likely to exhibit higher levels of job burnout.…”
Section: Discussionsupporting
confidence: 56%
“…This result supports the findings of some previous studies. 3 , 49 , 50 High levels of burnout among female nurses could be associated with their complex roles in Jordan: In addition to their professional responsibilities, females have more social responsibilities related to home and family than males. 51 , 52 Furthermore, more than 65% of the Jordanian population are children and women who require female nurses to meet their health needs.…”
Section: Discussionmentioning
confidence: 99%